Region VI Adult Education Staff Development Project Interim Report. - Texas Univ., Austin. Div. of Extension; Texas Univ., Austin. Div. of Extension ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The project provides for a five-State (Texas, Louisiana, Oklahoma, Arkansas, and New Mexico) consortium designed to upgrade competencies of all levels of Adult Basic Education (ABE) personnel. The major points of focus are: establishing bases for higher education; training State Department, university, and local ABE personnel by means of specialized institutes; making consultant expertise available to local ABE programs on a State and regional basis; and providing for technical services to local programs on a State and regional basis. The Division of Extension of the University of Texas at Austin agreed to oversee operations to ensure coordination and avoid duplication of effort. Each State department has designated a contact person for the regional coordinator. Funds were distributed among the participant States, and plans were constructed with the understanding that activities of common interest would be open to participants from all interested States. The major areas of emphasis in project implementation have been: support of higher education for classes and programs for adult education teacher preparation, workshops, and other inservice and preservice training, and support activities. The Region 6 Personnel Accounting and Control System was established to gather information on regional adult education personnel. (AG)
Sponsoring Agency: Bureau of Adult, Vocational, and Technical Education (DHEW/OE), Washington, DC.
Contract Number: OEG-0-72-1443.
Educational level discussed: Adult Basic Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Consortia; Program Descriptions; Regional Programs; Staff Development; Teacher Education; Teacher Improvement; Reports, Research